Analysis of the Causes and Conditions for the Formation of a High Incidence of Acute Respiratory Infections in the Population of the Altai Krai (Part 2. Environmental factors, diagnosis of coxiellosis and tickborne rickettsiosis) - A. I. Blokh; N. A. Pen'evskaya; N. V. Rudakov; S. V. Shtrek; S. N. Shpynov; O. F. Egorova; Kh. A. Manokhina; D. A. Saveliev; S. Yu. Krasotkina (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. Altai Krai (AK) is one of the least prosperous subjects of the Russian Federation in terms of the incidence of acute respiratory infections (ARI). Results of studying long-term and intra-annual dynamics of the incidence of ARI and community-acquired pneumonia (CAP) in various population groups of the AK in 2011–2021 led to a conclusion about possible connection between the characteristics of the epidemic process of ARI and environmental factors, primarily air pollution, as well as the widespread distribution of natural and atropurgic foci of tick-borne transmissible and zoonotic infections in the territory of the AK, along with the problems of diagnostics. Aim. Assessment of the possible influence of environmental factors on the formation of a high level of registered incidence of ARI in the Altai Territory, as well as diagnostics of some natural focal and zoonotic infections with fever and respiratory symptoms. Materials and methods. A retrospective epidemiological study was conducted based on annual and monthly official statistical reporting during 2011–2021 about the morbidity of the population, demographic and environmental features of the territory of the AK for each of the municipalities (MU), the average long-term incidence rates of ARI, VBP, tuberculosis, Siberian tick typhus (STT), ixodid tick-borne borreliosis, tick-borne viral encephalitis were calculated; appeals of the population regarding tick bites; population density and annual average sulfur dioxide (SO2) emissions. Pearson correlation coefficient was used to assess the strength of the relationship between the analyzed indicators; and seasonality coefficients and the method of trend-seasonal decomposition were used to assess the intra-annual dynamics of the incidence of ARI and CAP (for the period 2011-2019). To study seroprevalence of antibodies to C. burnetii, R. sibirica and SARS-CoV-2 in febrile patients with symptoms of ARI blood samples were collected in October 2022 from ten rural districts of the AK. Results and discussion. It was established that there was a significant direct correlation between the incidence of ARI and the amount of SO2 emissions into the atmosphere (r = 0.61, p < 0.001), as well as between the incidence of ARI and population density (r = 0.53, p < 0.001). The largest share (69%) of the total number of ARI cases in the Altai Territory in 2011–2021 was attributed to the cities of Barnaul, Biysk, Rubtsovsk, Zarinsk and Novoaltaisk, which are characterized by maximum SO2 emissions and population density. An additional contribution (8% total) to the incidence of ARI in the Altai Territory was attributed to 7 rural areas with the highest levels of SO2 emissions. Regardless of the ranking for the incidence of ARI and CAP, in 9 out of 10 areas selected for the study, patients had both anamnestic and diagnostic titers of antibodies to C. burnetii and/or R. sibirica. At the same time, coxiellosis cases in these areas were not registered for 12 years, and the number of cases of STT was much less than the probable number based on the proportion of patients which were seropositive to R. sibirica and had symptoms of ARI. IgM to SARS-CoV-2 were detected in 5 out of 203 examined samples, IgG – in 188 out of 203 examined samples, moreover 13.8% of samples had 118 to 499 BAU/ml, 40.9% of samples had 500 to 5000 BAU/ml, and the rest of samples had more than 5000 BAU/ml. Conclusion. Among all the variables analyzed in the study, the greatest role in the formation of the high level of registered incidence of ARI in the AK for many years belong to the high level of air pollution with SO2 emissions, high population density and, especially, their combination. Underdiagnosis of tick-borne rickettsioses and coxiellosis is of particular importance due to the unavailability of test kits for laboratory verification. Starting from 2020, a new coronavirus infection made some contribution to the registered incidence of ARI.